Strength development of dredged sediment stabilized with nano-modified sulphoaluminate cement - Lei Lang; Dan-Xuan Xue; Meng Dong; Wei Zhang; Jiang-Shan Li (Soils and Foundations)
Sulphoaluminate cement (SAC) is considered a low-carbon and energy-saving cementitious material, compared with ordinary Portland cement. However, the stabilization efficiency and improvement measures of SAC for dredged sediment (DS) are still unclear. This study used SAC as stabilizer for DS with high water content, and nanoparticles including nano-SiO2 (NS), nano-MgO (NM) and nano-Al2O3 (NA) were incorporated as nano-modifiers. Unconfined compressive strength (UCS) tests were carried out to evaluate the strength development of SAC-stabilized DS (SDS) and nano-modified SDS considering multiple influencing factors. Furthermore, the micro-mechanisms characterizing the strength development of SDS and nano-modified SDS were clarified and discussed based on X-ray diffraction (XRD) and scanning electron microscopy (SEM) tests. The results present that increasing SAC content or decreasing water content can obviously enhance the strength gaining of SDS, while the strength reduction also occurred. Incorporating suitable nanoparticles could significantly improve the strength gaining and simultaneously avoid the strength reduction of SDS. The optimum content of single NS, NM and NA was respectively 4 %, 6 % and 6 %. Composite nanoparticles containing two types of nanoparticles also exhibit positive effect on the strength gaining of SDS, and the optimum mass ratios of NS-NM, NS-NA and NM-NA were respectively 3:7, 1:9 and 5:5. By comparison, adding 6 % NA to SDS achieved the highest strength gaining. The hydration product ettringite was mainly responsible for the strength development of SDS and nano-modified SDS, and incorporating nanoparticles especially NA contributed to the formation of a tighter structure with stronger cementation inside nano-modified SDS. A conceptual model was proposed to characterize the micro-mechanism of strength development in nano-modified SDS.